A longitudinal analysis of growth and performance in selected and non-selected youth Rugby League players - Waldron, M.; Worsfold, P.; Twist, C.; Lamb, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Talent in team sport is often identified using longitudinal assessments of players` functional performances and anthropometric variables during adolescence. As little data exist in the sport of rugby league, there is scope to examine the factors that characterise higher ability, thus discriminating between selected and non-selected players at the youth level. Therefore, the purpose of the current study was to: (i) monitor the changes in anthropometric and performance measures in selected players over a three-season period, and (ii) identify the factors that differentiate between selected and non-selected players. Method: Following ethical approval, 28 under-15, -16 and -17 year-old elite youth rugby league players were assessed over three seasons of competition. The players, who were either coachselected or coach-non-selected at the end of each season, were annually tested for aerobic capacity, jump height, 10-30 m sprinting (velocity, acceleration, force and power) and anthropometric variables. Nine of the original sample were retained and played for the club at each age group. Results: A step-wise discriminant function analysis identified the selected players by 30 m sprinting force at under-15 (P=0.001) and squat jump height at under-16 (P=0.009). No factors characterised the selected players at under-17. Analysis of variance identified developments (P<0.05) in 10 m speed (d=6.3%), 10 m (d=13.9%) and 30 m force (d=10.8%), 10 m (d=19.9%) and 30 m power (d=14.5%), and concomitant changes in maturity (d=32% and d=25%) and stature (d=0.36% and d=0.12%) between the under-15 and under-16 seasons. Improvements (d=8.2%) in predicted VO2max between the under-16 and under-17 seasons were also evident alongside developments in quadriceps muscle cross-sectional area (d=16.3%) and lean mass (d=3.2%). Discussion: The results show the relative importance of force generation and explosive movements, such as vertical jumping, in identifying players of higher ability in the under 15 and 16 age groups which become less discriminative at the under 17 group. The results also show expected developments in physical size and aspects of performance in the under 15s to 16s group, which become limited to muscular growth at later stages. Practitioners should use the current results as a guide for developmental norms and consider the measurement of such performance characteristics to contribute to the identification of higher ability players, which will vary according to the age group. Given the disparity between players of the under 17 age group and adult populations, future research should evaluate the rate of development in growth and performance at more advanced age groups.